2019
DOI: 10.3390/plants8040104
|View full text |Cite
|
Sign up to set email alerts
|

Smoke-Water Enhances Germination and Seedling Growth of Four Horticultural Crops

Abstract: The impact of plant-derived smoke as a promoter of seed germination in many crops is well documented. However, very little is known about (1) the appropriate plant species for smoke-water preparation, (2) the effect of smoke-water on the germination and the post-germination parameters in non-fire-prone environments, and (3) the relative importance of dark and light conditions and their possible effects. To fill these gaps in knowledge, we conducted field experiments to evaluate the effect of smoke-water produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Smoke-water-treated tomato seedlings exhibited a remarkable increase in growth and yield [ 34 ]. Seedling mass was reported to be enhanced by smoke treatment in lettuce and cucumber [ 17 , 35 ]. Plant-derived smoke showed a promoting effect on edible banana by increasing the number of shoots [ 36 ], while, in onion, number, length and mass of leaves, and bulb diameter and weight was also increased in response to smoke treatment [ 35 ].…”
Section: Components In Plant-derived Smokementioning
confidence: 99%
See 1 more Smart Citation
“…Smoke-water-treated tomato seedlings exhibited a remarkable increase in growth and yield [ 34 ]. Seedling mass was reported to be enhanced by smoke treatment in lettuce and cucumber [ 17 , 35 ]. Plant-derived smoke showed a promoting effect on edible banana by increasing the number of shoots [ 36 ], while, in onion, number, length and mass of leaves, and bulb diameter and weight was also increased in response to smoke treatment [ 35 ].…”
Section: Components In Plant-derived Smokementioning
confidence: 99%
“…Seedling mass was reported to be enhanced by smoke treatment in lettuce and cucumber [ 17 , 35 ]. Plant-derived smoke showed a promoting effect on edible banana by increasing the number of shoots [ 36 ], while, in onion, number, length and mass of leaves, and bulb diameter and weight was also increased in response to smoke treatment [ 35 ]. Growth enhancement in horticultural crops suggested the possible use of smoke technology for cultivation and improvement of these crops.…”
Section: Components In Plant-derived Smokementioning
confidence: 99%
“…Studies have shown the impact of smoke originating from wildfire to restore the vegetation of fire-prone native species in the Mediterranean region [ 31 ]; Australia [ 32 ]; South Africa [ 33 ]; California [ 34 ]; and, the Mediterranean basin [ 35 ]. Additionally, its positive impact on the germination of cereal crops [ 2 , 36 ]; weed species [ 1 ]; horticultural crops [ 14 ]; and medicinal plants [ 37 ] has also been confirmed. The smoke-dependent germination process improves germination success across phylogenetically diverse plant groups including gymnosperms; angiosperms [ 33 ]; annuals; bi-annuals; short-lived species; and, perennial herbs [ 38 ], in different weather regions around the globe from tropical to the fire-prone Mediterranean region, disturbed habitats, representing a broad array of fire-prone environments [ 30 , 32 ].…”
Section: Role Of Smoke Smoke Generation and Componentsmentioning
confidence: 99%
“…The smoke-dependent germination process improves germination success across phylogenetically diverse plant groups including gymnosperms; angiosperms [ 33 ]; annuals; bi-annuals; short-lived species; and, perennial herbs [ 38 ], in different weather regions around the globe from tropical to the fire-prone Mediterranean region, disturbed habitats, representing a broad array of fire-prone environments [ 30 , 32 ]. Smoke has been used as an effective mediator to release dormancy in the laboratory [ 39 ] and field conditions [ 14 ]. Altogether, the germination response to smoke is not just associated with plant traits such as habitat requirements, seed bank, type, life form, and seed morphology, but also the chemical stimuli that alleviate the dormancy state.…”
Section: Role Of Smoke Smoke Generation and Componentsmentioning
confidence: 99%
See 1 more Smart Citation